The Panathenaic Pannychis - Valdés Guía, Miriam (ARYS. Antigüedad: Religiones y Sociedades, 2023)
An essential part of the night-time celebration of the Panathenaia was undoubtedly the chorus of young people, both parthenoi and neoi, on the acropolis during the night, probably on the eve of the great procession, and without ruling out the presence of mature women and old men as spectators and educators. These rites narrated the Acropolitan myths related to autochthony and to the birth of the goddess, her victory over the giants and her arrival and entry into the city. All these myths are, in a special way, related to the Cecropids. Possibly the night rites also included a dinner and a mimesis of the goddess in her armed dance of victory (the Pyrrhic dance). In addition, the pannychis may have been preceded by an informal procession from Pallene to the acropolis, a kallinikos komos, with a young woman dressed as Athena together with a young man (as Herakles), arriving by chariot to celebrate the night rites.
Keywords: Cecropids; Kallinikos komos; mimesis of Athena; pyrrhic dance; youth choirs